Clinical significance and related factors of rectal hyposensitivity in patients with functional defecation disorder - Jiang, Ya; Wang, Yan; Wang, Meifeng; Lin, Lin; Tang, Yurong (Frontiers in Medicine, 2023)
Background: Rectal hyposensitivity (RH) is not uncommon in patients with functional defecation disorder (FDD). FDD patients with RH is usually unsatisfied with their treatment. Aims: To find the significance of RH in FDD patients and the related factors of RH. Methods: Patients with FDD firstly completed clinical questionnaires regarding constipation symptoms, mental state and quality of life. Then anorectal physiologic tests (anorectal manometry and balloon expulsion test) were performed. Rectal sensory testing (assessing rectal response to balloon distension using anorectal manometry) was applied to obtain three sensory thresholds. Patients were separated into 3 groups (non-RH, borderline RH and RH) based on London Classification. The associations between RH and clinical symptoms, mental state, quality of life and rectal/anal motility were investigated. Results: Of 331 included FDD patients, 87 patients (26.3%) had at least one abnormally elevated rectal sensory threshold and 50 patients (15.1%) were diagnosed as RH. Patients with RH were older and mostly males. Defecation symptoms were more severe (P=0.013) and hard stool (P<0.001) and manual maneuver (P=0.003) were more frequently seen in RH group. No difference of rectal/anal pressure was found among 3 groups. Elevated defecatory desire volume (DDV) existed in all RH patients. With numbers of elevated sensory thresholds increasing, defecation symptoms got more severe (r=0.35, P=0.001). Gender (male) (6.78[3.07-15.00], P<0.001) and hard stool (5.92[2.28-15.33], P<0.001) were main related factors of RH. Conclusions: RH plays an important role in the occurrence of FDD and is associated with defecation symptom severity. Old male FDD patients with hard stool are prone to suffering RH and need more care.